Prevalence and serotyping of Salmonella in beef carcasses sold in markets of Hama city, Syria - O. Faour; Kh. Alkoujah (Теория и практика переработки мяса)
Salmonella is one the most important pathogenic bacteria, which causes food poisoning in human consumers worldwide. This study aimed to detect the prevalence and serovars of Salmonella in beef in markets of Hama city, Syria. The study was carried out on 200 beef samples from 20 retail shops in markets of Hama city, Syria. Investigation was conducted using bacterial cultures and serotyping. Bacterial cultures showed that 11 samples out of 200 samples from different retail shops were positive, with an overall prevalence of 5.5% (95% CI: 2.34–8.66). The isolated serotypes were S. Typhimurium (36.36%), S. Enteritidis (27.27%), S. Reading (9.09%), S. Bredeney (9.09%), S. Chester (9.09%), and S. Anatum (9.09%). Significantly higher (p<0.05) prevalence was revealed in the east district (8%, 4/50) compared to other districts, in informal shops (7.5%, 6/80) than in other outlets, in female animals (10%, 4/40) compared to male animals, in slaughtered animals at the age of more than 12 months (7.5%; 6/80), in summer (12%, 6/50) compared to other seasons, in unclean shops (7.38%, 9/122), and in liver (7.5%, 6/80) compared to other meat types. These results are considered an important threat to public health and indicate food contamination.